Histological analysis of induced membranes in patients whose bone defects were treated with the Masquelet technique to identify factors affecting the vascularity of induced membranes - Niikura, Takahiro (J Orthop Surg Res, 2021)
BACKGROUND: Rich vascularity of the induced membrane (IM) is important for Masquelet reconstruction surgery. The factors affecting IM vascularity are not completely understood. This study aimed to investigate these factors using histological samples of human IMs. METHODS: We retrospectively evaluated 36 patients whose bone defects were treated using the Masquelet technique. Two clinical pathologists analyzed histological sections of IM pieces (1 cm(2)). The number of blood vessels per 1 mm(2) was counted and compared among men and women, femur or tibia, with and without free flap surgery, antibiotic impregnation to the cement, osteogenesis inside the membrane, smoking, and diabetes mellitus. The number of blood vessels within the same patient was compared among different time points. Correlation analysis was performed among blood vessel numbers and patient age, duration of cement spacer placement, and histological grading scales (inflammation, foreign body reaction, and fibrosis). RESULTS: IM formation with rich vascularity and some inflammation, foreign body reaction, and fibrosis were histologically confirmed in all patients. We found 37.4 ± 19.1 blood vessels per 1 mm(2). The number of blood vessels was significantly lower in patients with than in those without free flap surgery; it was higher in patients with osteogenesis inside the IM. No significant correlations were found in any of the analyses. CONCLUSION: Sex, patient age, smoking, diabetes mellitus, femur or tibia, duration of cement spacer placement, and antibiotic impregnation to the cement did not affect IM vascularization. IM vascularization was reduced in patients with than in those without free flap surgery.